Common Structural Deficiencies Identified in Canterbury Buildings and Observed versus Predicted Performance. Issue 1 (February 2014) - Bech, Dan; Cordova, Paul; Tremayne, Bill; Tam, Kenneth; Weaver, Benjamin; Wetzel, Nicholas; Parker, Will; Oliver, Lisa; Fisher, Jenny
This paper presents a list of common structural deficiencies identified following the Canterbury earthquakes. The deficiencies are based on detailed engineering evaluations of hundreds of buildings in Christchurch and its surrounding areas. The deficiencies identified are common to some of the more prominent collapses but are also found in buildings with limited or concealed damage. The detailed evaluations identified these deficiencies and limited the occupancy, triggered strengthening, or lead to the demolition of the structure. In addition, this paper includes a comparison of observed versus predicted performance of three concrete buildings in the Christchurch area that survived the Lyttelton event with limited damage. The predicted performance utilizes nonlinear time history analysis and is relative to the acceptance criteria specified in ASCE 41-06. In general, the observed performance was found to be better than the predicted. Sources of uncertainty and potential conservatism are evaluated including foundation stiffness, kinematic effects, and vertical accelerations.